Health and Psychosocial Self-Care Needs in Off-Therapy Childhood Cancer: Hybrid Model Concept Analysis - Akbarbegloo, M (Patient Prefer Adherence, 2020)
PURPOSE: The self-care concept is a complicated and multi-dimensional phenomenon. There are different opinions about self-care needs; therefore, this study was conducted to clarify the self-care needs of the off-therapy childhood cancer survivors based on the hybrid model. PATIENTS AND METHODS: There are three phases in the hybrid model including literature review, fieldwork, and final analysis. At the theoretical phase, 119 articles in databases were evaluated without time limits up to August 2019. At the fieldwork phase, 19 participants were selected with purposive sampling and interviewed through unstructured interviews. Then, the data were analyzed by qualitative content analysis approach. In the final phase, the overall analysis of the two previous phases was carried out and the ultimate definition of self-care needs was presented with the integration of the results of two previous phases. RESULTS: Theoretical results showed that self-care needs are those that need to be performed by off therapy childhood cancer in everyday life in order to maintain health and well-being through the practice of healthy behaviors and activities. Also, fieldwork results indicated that self-care needs are increased due to the physical, mental, and social vulnerability of the disease. Following that, the need for protective self-care behaviors to prevent against physical and psychosocial side effects arises. If the patients are unable to implement protective behaviors, the need for support from others is created. Therefore, by synthesizing the findings of literature review and fieldwork, self-care needs are two-dimensional concept: (1) need for changing in behavior to protect themselves against physical and psychosocial distress and (2) need for supporting to implement care. CONCLUSION: Taking into account the self-care needs, healthcare providers can support childhood cancer survivors in gaining and maintaining independency in self-care. On the other hand, the results of this study by creating a basic knowledge in the field of self-care needs can be used in the development of policy and standards of care to meet the needs of this group.